Investor sentiment under the Maqasid Al-Shari’ah compliance asset pricing model: a behavioral finance approach to Islamic finance / Igo Febrianto, Norhayati Mohamed and Imbarine Bujang - Febrianto, Igo; Mohamed, Norhayati; Bujang, Imbarine (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
This study provides perspectives and insights into the importance of Maqasid al-Shari’ah in the discourse of Shari’ah-Compliant Asset Pricing Model (SCAPM) development by considering inflation and zakat as the minimum level of expected return. The study also integrated market risk and investor sentiment as systematic risks faced by Muslim investors in stock investments. Using a non-linear panel ARDL approach with monthly panel data from 109 Shari’ah-compliant listed companies on the Indonesian Stock Exchange between October 2007 and June 2021 (164 months), the study found that the Islamic market risk premium and investor sentiment had a positive long-term impact on Shari’ah-compliant stock returns. Surprisingly, market risk premium had a reverse effect in the short term, while investor sentiment remained positive. These findings contribute to understanding Islamic finance and have practical implications for investors, financial institutions, and policymakers.